TARGET2 Balances : Analysis of Causes and Possible Consequences - Novák, Petr (2018)
Increasing TARGET2 imbalances and their potential consequences have been a relatively new topic since the financial crisis in 2007. The goal of this thesis was to analyse the causes and possible consequences of TARGET2 imbalances by analysing the ECB’s monetary policy and balance of payments of southern European countries which accumulated greatest TARGET2 liabilities. TARGET2 imbalances have been significantly accumulating from 2007 to 2013. Then, until 2015, the imbalances have been decreasing. However, the TARGET2 imbalances have been increasing again since 2015 despite the economic growth in the eurozone. From my analysis, it appears that there were two different reasons of the imbalance increase depending on the period. After the financial crisis in 2007, the imbalance was caused by an outflow of financial capital from southern European countries. However, after 2015, the imbalance has been mainly caused by the ECB’s asset purchase programme. If the TARGET2 claims were to be written-off, the loss would be redistributed among central banks of the eurozone.